Anthony Giddens and international relations: structuration, modernity and globalization - EMRE, YUNUS (Uluslararası İlişkiler Konseyi Derneği, Söğütözü Cad No 43, Tobb-Etü Binası, Oda No 364, Söğütözü, Ankara 06560, Turkey, 2015)
This paper aims to examine the subjects which are pertaining to International Relations in the works of Anthony Giddens and also to evaluate different uses of such issues in the International Relations literature. As one of the prominent social theorists of the 20th century, Giddens had. significant influence on International Relations in terms of his structuration theory, modernity and nation-state approach and his views on globalization. The article is organized in four parts. In the first part, Anthony Giddens' structuration theory is examined. In the second part, Giddens' historical and theoretical interpretations on modernity, nation-states and the relations among nation-states are scrutinized. The third part is about the globalization approach of Giddens. In the fourth part, the use of Giddens' contributions with regard to International Relations studies are evaluated.
Keywords: Anthony Giddens; Social Theory; Structuration; Theory of International Relations